Main neurological manifestations associated with SARS-CoV-2 (COVID-19): a narrative review of the literature - Santos Neto, Manoel Pereira dos (2022)
Introduction: Infection with the new coronavirus has a heterogeneous, multifactorial character and, despite greater respiratory compromise, it constitutes a multisystem involvement that can affect the nervous system, generating complex sequelae. Objective: to address the main neurological manifestations of COVID-19, for a better understanding of the disease by health professionals and academics. Methodology: this is a literature narrative, carried out from the search for scientific publications indexed in the databases: PubMed, MEDLINE, Scielo, CDSR, Google Scholar, BVS and EBSCO. The following descriptors were used: with the descriptors "SARS-CoV-2", "neurological symptoms", "COVID-19", "spike protein", "ACE2". At the end of the searches, 40 publications met the eligibility criteria and were selected to compose the study. Results: in view of the findings extracted from the selected studies, it was noticed that the most frequently reported neurological manifestations are: headache, anosmia, ageusia and occurrence of cerebrovascular events (CVA, CVT). In addition, SARS-CoV-2 infection has also been linked as a risk factor for the occurrence of Guillain-Barré Syndrome, encephalitis, and changes in levels of consciousness. Conclusion: this study allowed us to reflect on the variety of neurological manifestations caused by COVID-19, as well as the complexity involved in the management of this disease. It is suggested to carry out more detailed studies on the subject in order to better clarify the findings and clinical management to be adopted.